Bearing Fault Analysis in Induction Motor Drives Using Finite Element Method - Vinothraj, C; Praveen Kumar, N; B. Isha, T (International Journal of Engineering and Technology, 2018)
Diagnosis of faults in induction motor is an indispensable process in industries to improve the reliability of the machine and reduce the financial loss. Among the various faults occurring in induction motors (IM), bearing fault is the predominant one which covers nearly 60% of faults. In this paper, a study of the electromagnetic field of an induction motor with bearing fault fed from both the mains and a three phase voltage source PWM inverter in open loop is carried out using Finite element method (FEM). Electromagnetic field parameters like flux lines distribution, flux density distribution and radial air gapflux density are analyzed. The presence of bearing fault can be detected from the spatial FFT spectrum of radial air gap flux density. From the FFT spectrum, it is seen that the amplitude of fundamental component of radial air gap flux density decreases and those around 100 mm distance increases with the severity of fault.Â Â